The role of nurse shrubs on the spatial patterning of plant establishment in semi-arid gypsum plant communities. (January 2019) - Foronda, Ana; Pueyo, Yolanda; Arroyo, Antonio I.; Saiz, Hugo; Giner, María de la Luz; Alados, Concepción L.
Abstract: Plants may depend on nurse plants to establish and survive on gypsum environments, which are stressful for plant life. Shrubs may act as nurse plants by ameliorating micro-environmental conditions in their local vicinity. Despite its importance, the role of nurse shrubs on the spatial patterning of plant establishment remains largely unknown in gypsum communities. Our aim was to understand the patterns of plant establishment and to identify key nurse species in facilitating plant establishment and structuring plant diversity at community level in these environments. We set an observational study in two gypsum plant communities of NE Spain to assess the microsites where seedlings germinate. Also, we assessed the role of six dominant shrubs (gypsophytes and gypsovags), in spatially structuring plant diversity by assessing species-area relationships in their local vicinity to identify key nurse species. To assess the potential amelioration of micro-environmental conditions associated to shrubs, we analyzed physical-chemical soil properties under shrub canopies compared to open areas. Most plants were spatially associated with adult shrubs. Gypsophytes accumulated more diversity than gypsovags, despite both showing ameliorated conditions under canopy compared to open areas. In conclusion, gypsophyte shrubs play key roles in the structure of gypsum plant communities by facilitating plant establishment. Highlights: Regardless of the life strategy, plants are facilitated in gypsum communities. Gypsophyte shrubs facilitate the establishment of annual and perennial plants. Diversity in gypsum communities accumulates in the vicinity of gypsophyte shrubs.